Impact of Cyber Relational Addiction on Undergraduates’ Interpersonal Relationship in Nigeria - Mustapha, Mulikat Ladi Abdulqadir; Ajokpaniovo, Michael; Olaoye, Faith Elizabeth (Jurnal Kajian Bimbingan dan Konseling, 2022)
The upsurge in the use of cyberspace in recent years has led to pathological use for some individuals especially in the area of cyber relational addiction. This study aimed to investigate the influence of cyber relational addiction on interpersonal relationships and how variables of age, religion, levels of study, and gender of respondents moderate the influence of cyber relational addiction on their interpersonal relationships. This study employed a descriptive survey research design and administered a self-designed questionnaire on 420 randomly selected undergraduates from seven faculties at the University of Ilorin. A research question was answered in this study, while the hypotheses were also tested at 0.05 levels of significance. The varying collected data were analyzed using t-test and Analysis of Variance (ANOVA) statistical methods. Undergraduate students’ sources of information were mostly from the Internet than interacting with people, and they believed gaining more academically online than interacting with people. Meanwhile, the results were not varied based on the respondents’ age, levels of study, religion, and gender. It is necessary to develop a sound and wide range of activities that will reduce cyber relation addiction, which in turn promote psychological wellbeing among undergraduates. Interpersonal relationship skills training should be conducted for cyber-addicted adolescents to observe its impacts on cyber relational addiction.